2021
DOI: 10.1155/2021/5031479
|View full text |Cite
|
Sign up to set email alerts
|

NMU Is a Poor Prognostic Biomarker in Patients with Lung Adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is the most prevalent histologic type of lung cancer, associated with a high incidence rate and substantial mortality rate worldwide. Accumulating evidence shows that the aberrant expression of neuromedin U (NMU) contributes to the initiation and progression of cancer. Herein, we explored whether NMU could be adopted as a new diagnostic and therapeutic marker in LUAD. The UALCAN and GEPIA web resources were employed to assess data on the NMU expression in LUAD. The STRING web resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recent studies have reported NMU expression in various organs and tissues was a kind of poor prognosis of lung cancer markers. 11 According to the study, NMU also regulates the development of lung adenocarcinoma CAMP signal pathway and has close ties to lung adenocarcinoma cell proliferation. 12 UBE2C affects the cell cycle of renal cell carcinoma and migration and promotes carcinogenesis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported NMU expression in various organs and tissues was a kind of poor prognosis of lung cancer markers. 11 According to the study, NMU also regulates the development of lung adenocarcinoma CAMP signal pathway and has close ties to lung adenocarcinoma cell proliferation. 12 UBE2C affects the cell cycle of renal cell carcinoma and migration and promotes carcinogenesis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NMU inhibits the growth of these tumor cells. However, in bladder cancer ( 46 ), endometrial carcinoma ( 47 , 48 ) and breast cancer ( 49 ), lung adenocarcinoma ( 50 ), NMU overexpression can promote tumor cell growth, enhance tumor formation and metastasis, and increase tumor drug resistance. The latest study found for the first time that NMUR2 activation promoted signaling in colorectal cancer (CRC) cells, and that NMU improves the mobility and invasiveness of NMUR2-positive CRC cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the treatment of LUAD patients has made great progress, including surgery, radiotherapy, chemotherapy, or targeted therapy [ 4 , 5 ]. However, the outcomes of patients with LUAD recurrence are still poor [ 6 ]. Recent research has confirmed the potential of the targeted therapy, which blocks the upgrowth of lung cancer cells by inhibiting the initiation of vital oncogenic molecules that drive the progression of LUAD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the outcomes of patients with LUAD recurrence are still poor [ 6 ]. Recent research has confirmed the potential of the targeted therapy, which blocks the upgrowth of lung cancer cells by inhibiting the initiation of vital oncogenic molecules that drive the progression of LUAD [ 6 ]. Although targeted therapy has achieved gratifying results in the early treatment of LUAD and shown promising potential, drug resistance's existence and continuous development often directly lead to treatment failure [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%